THE METHODOLOGY OF TEACHING ECONOMIC TERMS IN ENGLISH - Alimardonova Maftuna Bekmurodovna (Galaxy International Interdisciplinary Research Journal, 2021)
This article examines the issue of the practical use of the English language in modern society.The question is raised about the need for a new approach to teaching foreign languages, due to the development of the world economic system, as well as the development of the education system as a whole. The peculiarities of teaching English to law students are also considered.